Strategi Peningkatan Mobilitas Fisik dan Pencegahan Jatuh Pada Lansia di BPSTW Budi Luhur Daerah Istimewa Yogyakarta - Fauziya Azzahra, Rahma; Riyadi, Sujono (Jurnal Indonesia Sehat, 2024)
Background: The elderly experience a decrease in physical condition that can cause mobility impairment and increase the risk of falls. Objective: This study aims to implement strategies to increase physical mobility and prevent falls in the elderly at BPSTW Budi Luhur Yogyakarta. Methods: The method used was nursing care with intervention of mobilization support and balance exercises Tandem Stance Exercise for six days. Result: The results showed an increase in physical mobility and a decrease in fall risk based on the Morse Fall Scale (MFS), from a score of 65 (high risk) to 45 (low risk). In addition, patients experience increased postural stability and confidence in movement. Conclusion: This intervention has been shown to be effective in improving balance and reducing the risk of falls in the elderly. It is recommended that balance exercises be carried out regularly to improve the quality of life of the elderly.